Clinical Investigation of a Rapid Non-invasive Multispectral Imaging Device Utilizing an Artificial Intelligence Algorithm for Improved Burn Assessment - Thatcher, Jeffrey E; Yi, Faliu; Nussbaum, Amy E; DiMaio, John Michael; Dwight, Jason; Plant, Kevin; Carter, Jeffrey E; Holmes, James H (Journal of burn care & research, 2023)
Abstract Currently, the incorrect judgment of burn depth remains common even among experienced surgeons. Contributing to this problem are change in burn appearance throughout the first week requiring periodic evaluation until a confident diagnosis can be made. To overcome these issues, we investigated the feasibility of an artificial intelligence algorithm trained with multispectral images of burn injuries to predict burn depth rapidly and accurately, including burns of indeterminate depth. In a feasibility study, 406 multispectral images of burns were collected within 72 hours of injury and then serially for up to 7 days. Simultaneously, the subject’s clinician indicated whether the burn was of indeterminate depth. The final depth of burned regions within images were agreed upon by a panel of burn practitioners using biopsies and 21-day healing assessments as reference standards. We compared three convolutional neural network architectures and an ensemble in their capability to automatically highlight areas of nonhealing burn regions within images. The top algorithm was the ensemble with 81% sensitivity, 100% specificity, and 97% positive predictive value (PPV). Its sensitivity and PPV were found to increase in a sigmoid shape during the first week postburn, with the inflection point at day 2.5. Additionally, when burns were labeled as indeterminate, the algorithm’s sensitivity, specificity, PPV, and negative predictive value were: 70%, 100%, 97%, and 100%. These results suggest multispectral imaging combined with artificial intelligence is feasible for detecting nonhealing burn tissue and could play an important role in aiding the earlier diagnosis of indeterminate burns.